The Physical and Chemical Characteristic of Al-Garraf River Water at Waist Province Canal - M. Salman, Rasha; S. AL-Sariy, Jameel; R. Nashaat, Muhanned (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Monthly variations in Physio-chemical parameters of Al-Garraf water in Waist province, one of the main tributaries of the Tigris River to investigate the water quality of the river from August 2014 to January 2015. The study location situated in the southeastern sector of Iraq and surrounded by wide and fertile agricultural lands. Three stations were selected for collecting samples monthly, samples were taken each month. Station one is located at 500 m of the AL - KUT Dam. The second is situated at distance of 15 Km away from the former (Kut- Muwafaqiya) and the latter station is located at 18 Km apart from the second one upon entering the river hand Muwafaqiya. In the present study fourteen physical and chemical parameters were analyzed based on the importance of these parameters. These fourteen parameters are ranged as following: Air temperature (12 to 37.2) ºC, water temperature (12.1 to 28.4) ºC, pH (7.2 to 7.8), EC (490 to 1860) µS/cm, Salinity (0.64 to 1.19) ‰, DO (2.7 to 9.3) mg/L, BOD5 (0.2 to 7.1) mg/L, Turbidity (21.44 to 74) NTU, TDS (0.580 to 0.99 ) g/L, TSS (0.0006 to 0.059) mg/L, TH (388 to 504) µg/L, Ca+2 (100 to 160.32) mg/L, Mg+2 (3.69 to 52.07) mg/L and NO3-2 (0.034 to 3.69) mg/L and PO4-2 (0.015 to 0.225) µg/L. , Bicarbonate (130 to 180) mg/L , Sulfate (80 to 180) mg/L, the percentage of oxygen saturation (32.25 to 306.29) % ,Water flow (2.5 to 10.7)m. and total Alkalinity(12.2 to 25)mg/L. The results revealed that water parameters were within the Iraqi standards for the raw water.